Link between small-vessel vasculitides and atherosclerosis. (February 2008) - Pagnoux, Christian; Chironi, Gilles; Simon, Alain; Guillevin, Loïïc
Premature atherosclerosis has recently emerged as a late, but possibly severe, complication of systemic small-vessel vasculitides, mainly represented by Wegener''s granulomatosis, microscopic polyangiitis and Churg––Strauss syndrome. We review herein the different mechanisms that might contribute to the formation of atherosclerotic lesions in those latter and rare diseases. Chronic systemic and local endothelial inflammation observed in vasculitides probably plays a major role. Other immune system dysregulations, but also endothelial dysfunction and, perhaps, defects in the capacity to repair the injured endothelium might also contribute to the pathogenesis of premature atherosclerosis. Treatments for vasculitis, especially corticosteroids, can induce or aggravate hypertension or diabetes and known cardiovascular risk factors; but it is unclear whether they also favor atherosclerosis directly. Prevention, early detection and treatment of premature and accelerated atherosclerosis should now definitely be viewed as one of the primary objectives of the long-term management of vasculitis patients.